Economic Welfare of Refugees and Nationals in Kenya: A Comparative Panel Data Analysis - Suleiman Hassan Maalim (Economies, 2025)
This study investigates the economic welfare of refugees and host communities in Kenya, utilizing bi-monthly panel data collected from May 2020 to May 2022. The analysis employs a fixed effect model, which effectively captures the nuances of welfare differences between urban and camp refugees. The key findings reveal that income and economic participation are critical determinants of welfare, with urban refugees exhibiting greater sensitivity to income fluctuations compared to their camp counterparts. Larger household sizes negatively impact welfare, while education levels and gender dynamics play pivotal roles. This study emphasizes the need for tailored interventions for economic empowerment, particularly for women-headed households, and highlights the importance of partnerships between NGOs and local governments. Overall, this research enhances the understanding of refugee welfare in Kenya and provides actionable policy suggestions aimed at promoting equity and integration.